2001
DOI: 10.1093/humrep/16.9.1995
|View full text |Cite
|
Sign up to set email alerts
|

Relative risk of conversion from normoglycaemia to impaired glucose tolerance or non-insulin dependent diabetes mellitus in polycystic ovarian syndrome

Abstract: Women with PCOS, particularly those with a high BMI, should be reviewed regularly with respect to IGT or NIDDM, as the frequency of impaired glycaemic control is high, and that the rate of conversion from normal glucose tolerance to IGT or NIDDM, or from IGT to NIDDM is substantial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
158
1
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(175 citation statements)
references
References 15 publications
5
158
1
11
Order By: Relevance
“…The risk for deteriorated glucose tolerance was high during follow-up in PCOS (14,24). American patients with PCOS had an 8-year incidence of 13.4% for T2D (25) and 16.4% Australian patients with PCOS developed T2D during 6 years of follow-up (24). In these studies, the most important predictive factor for the development of T2D was obesity (14,24).…”
Section: Cardiometabolic Disease In Pcosmentioning
confidence: 81%
See 1 more Smart Citation
“…The risk for deteriorated glucose tolerance was high during follow-up in PCOS (14,24). American patients with PCOS had an 8-year incidence of 13.4% for T2D (25) and 16.4% Australian patients with PCOS developed T2D during 6 years of follow-up (24). In these studies, the most important predictive factor for the development of T2D was obesity (14,24).…”
Section: Cardiometabolic Disease In Pcosmentioning
confidence: 81%
“…In the general population, around 5-10% individuals with pre-diabetes convert to diabetes per year and up to 70% individuals with pre-diabetes will develop diabetes (23). The risk for deteriorated glucose tolerance was high during follow-up in PCOS (14,24). American patients with PCOS had an 8-year incidence of 13.4% for T2D (25) and 16.4% Australian patients with PCOS developed T2D during 6 years of follow-up (24).…”
Section: Cardiometabolic Disease In Pcosmentioning
confidence: 99%
“…Several relatively small studies have shown an increase in IGT and the development of type 2 diabetes amongst PCOS patients, particularly in subjects with a positive family history (49,50,51,52,53,54). The AE-PCOS Society consensus statement (12) recommends a 2 h post-75 g oral glucose challenge to be performed in PCOS women with a BMI O30 kg/m 2 , or alternatively in lean PCOS women with advanced age (O40 years), personal history of gestational diabetes, or family history of type 2 diabetes.…”
Section: Type 2 Diabetes Risk and Pcosmentioning
confidence: 99%
“…IR constitutes a prerequisite for diabetes mellitus (DM) and/or metabolic syndrome development, and consequently the increased incidence of these two morbidities in women with PCOS, compared with their BMI-matched peers, is expected (5,6,7,8,9). However, the available prospective studies reporting the significantly higher incidence of DM in women with PCOS compared with general population are few and DM is found mainly in obese women with the syndrome (10,11,12).…”
Section: Introductionmentioning
confidence: 99%